Effects of murine recombinant interleukin 1 on synovial joints in mice: measurement of patellar cartilage metabolism and joint inflammation. - van de Loo, A A (1990)
Murine recombinant interleukin 1 was injected intra-articularly into mice. It induced a clear effect on patellar cartilage within 24 hours. A low dose of interleukin 1 (1 ng) elicited a significant reduction in [35S]sulphate incorporation (50%) into proteoglycans and an accelerated breakdown (twofold) of 35S prelabelled proteoglycan. Proteoglycan breakdown returned to normal rates (approximately 10%/day) 48 hours after a single interleukin 1 injection. Recovery of proteoglycan synthesis was delayed by up to 72 hours, however, which implies that repair of the depleted cartilage matrix is retarded. Interleukin 1 induced only minor joint inflammation, too slight to be held responsible for the strong suppression of proteoglycan synthesis. Vehement joint inflammation was found after repeated interleukin 1 injections. The plasma extravasation and massive infiltration and exudation of leucocytes, predominantly polymorphonuclear leucocytes, were not a mere summation of single interleukin 1 effects, but point to interleukin 1 induced local hypersensitivity. The cartilage matrices of patella and femur were heavily depleted. Measurement of the extent of loss of 35S prelabelled proteoglycan and the prolonged inhibition of [35S]sulphate incorporation indicate that both inhibition of proteoglycan synthesis and enhanced loss of proteoglycan contributed substantially to this depletion.